Air Pollution Calculation for Location Based Social Networks Multimodal Routing Service - Brito, Matheus; Santos, Camilo; Oliveira, Helder; Cerqueira, Eduardo; Rosário, Denis (Anais do Workshop de Computação Urbana (CoUrb), 2022)
With the growth of the urban population, the urban mobility infrastructure suffers several types of problems, such as the more significant occurrence of traffic jams, which directly affects the quality of life of the population and the inhabitants who need to use different types of transport, also generating a more extraordinary occurrence of air pollution emitted by vehicles. This work addresses the need to integrate the generation of hybrid multimodal routes through the analysis of geographic data collected from location-based social networks, adding the calculation of greenhouse gas emissions by used vehicles. Further, performs a user experience analysis for the main identified flows of the analyzed urban environment, for users and urban planners analysis. The proposed algorithm proves its efficiency by offering less expensive, healthier trips for the population.